2014
DOI: 10.1016/j.gloplacha.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Record of methane emissions from the West Svalbard continental margin during the last 23.500yrs revealed by δ13C of benthic foraminifera

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 83 publications
4
62
0
Order By: Relevance
“…The effect of authigenic carbonates on the isotopic composition of foraminiferal shells has been identified previously (e.g. The record of Consolaro et al (2015) showed indications of higher methane flux in sediments belonging to the end of the Allerød interstadial in the western part of the Vestnesa Ridge, while Panieri et al (2014) found the highest flux to occur in the lower Bølling interstadial as indicated by the distribution patterns and biostratigraphical correlation of the benthic foraminiferal faunas. However, authigenic overgrowth is not widely discussed and most studies from seep environments focus on benthic foraminifera without simultaneous measurements of the planktonic foraminifera, assuming that the entire depleted d 13 C signal is a result of calcification in pore water with DIC of very low d 13 C values (Hill et al 2004;Martin et al 2007Martin et al , 2010Panieri et al 2009Panieri et al , 2012.…”
Section: Mass Transport Depositssupporting
confidence: 64%
See 3 more Smart Citations
“…The effect of authigenic carbonates on the isotopic composition of foraminiferal shells has been identified previously (e.g. The record of Consolaro et al (2015) showed indications of higher methane flux in sediments belonging to the end of the Allerød interstadial in the western part of the Vestnesa Ridge, while Panieri et al (2014) found the highest flux to occur in the lower Bølling interstadial as indicated by the distribution patterns and biostratigraphical correlation of the benthic foraminiferal faunas. However, authigenic overgrowth is not widely discussed and most studies from seep environments focus on benthic foraminifera without simultaneous measurements of the planktonic foraminifera, assuming that the entire depleted d 13 C signal is a result of calcification in pore water with DIC of very low d 13 C values (Hill et al 2004;Martin et al 2007Martin et al , 2010Panieri et al 2009Panieri et al , 2012.…”
Section: Mass Transport Depositssupporting
confidence: 64%
“…Torres et al 2003;Martin et al 2004;Uchida et al 2008). The events of low d 13 C values are located at different depths below the sediment surface in the various studied records, yet the timing of the event is similar: 390 cm in the core of Consolaro et al (2015), 108-247 cm in the core of Panieri et al (2014) (the SMTZ today is found 65 cm down-core), 85 and 225-230 cm in core JM10-335GC and 115-125 cm in core HH12-929GC (Fig. Alteration of the foraminiferal shells could have occurred soon after the foraminifera died or at any time during modern venting (Martin et al 2004).…”
Section: Mass Transport Depositsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, the absence of benthic foraminifera in Unit I is also suggested aerobic oxidation of methane induced suboxic conditions (Li et al, unpublished data). The abundance of benthic foraminifera in modern intensive cold seep activity environment is typically low (Panieri et al, 2014). The absence of authigenic carbonate in study core may be due to the low efficient AOM, which induce the low alkalinity, or acidic environment caused by aerobic oxidation of methane, just like the cold seeps in convergent margin off Costa Rica and calcium carbonate dissolved in PETM (Zachos et al, 2005;Karaca et al, 2010;Consolaro et al, 2015).…”
Section: Aerobic Oxidation Of Methane In An Aom-dominated Environmentmentioning
confidence: 94%